Relación del consumo alimentario con el riesgo cardiovascular en pacientes adultos del Centro de Salud N. 11 de la ciudad de Guayaquil, periodo noviembre 2023 - abril 2024. - Banderas Montoya, Nayelhy Nathaly (2024)
The present investigation deals with the relationship between dietary intake and cardiovascular risk in adult patients; our study variables generate a high impact on our society since our sector has as prevalence pathologies such as overweight, obesity, diabetes mellitus type II, hypertension, dyslipidemias which are risk factors for cardiovascular disease and generates a problem for our population in addition to our country Ecuador has a history that cardiovascular disease has been the leading cause of mortality for the year 2018, worldwide for the year 2016 approximately 17.9 million deaths were caused mainly by myocardial infarction and stroke according to WHO. While these NCDs are the result of several factors that may or may not occur simultaneously, diet and lifestyle play a key role. Unhealthy diet and bad habits are the main triggers or can lead to further complications. The objective of our research project is to determine the relationship between dietary intake associated with cardiovascular risk in adult patients aged 35-50 years old from the N11 health center in the city of Guayaquil, whose type of research will be applied, field, descriptive, exploratory and cross-sectional and will use inductive and analytical methods. The online survey created, structured and validated by the Spanish Society of Food Science and Anthropometric Measurements for the waist/hip ratio will be used to obtain data.